A Framework to Assess the Seismic Resilience of Urban Hospitals - Peng Yu; Weiping Wen; Duofa Ji; Changhai Zhai; Lili Xie (Advances in Civil Engineering)
The phenomenon of hospital functional interruption has been widely observed in the historical moderate-strong earthquakes, indicating that hospital functionality cannot be well considered in the current seismic design methods. The concept of seismic resilience pays enough attention to postearthquake functionality of buildings, and it is particularly significant for the urban hospitals which play critical role in the urban postearthquake rescue and recovery. This study proposes a framework to assess the seismic resilience of urban hospitals, by incorporating the fault tree analysis (FTA) to consider the interdependency between the damage of nonstructural components and the functionality of medical equipment, as well as the effect of external supplies on the functionality of hospital. The proposed framework is then applied to a case-study hospital, and the results indicate that this hospital needs 1.1 days to resume emergency functionality under REDi repair strategy after design basis earthquake (DBE), while it needs 28.8 days to resume emergency functionality under REDi repair strategy after maximum considered earthquake (MCE). It is found that the seismic resilience of this hospital after MCE cannot meet the community requirements on the recovery time, and necessary measures are needed to improve the seismic resilience. The proposed framework provides the quantitative results of seismic resilience assessment in the preearthquake environment and can further support emergency response planning and seismic retrofits strategies.